BOOK REVIEW: EXPLICIT LEARNING IN THE L2 CLASSROOM - Prasetyo, Hardi (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2019)
This book provides a theoretically framed and empirically supported approach to support explicit learning (learning with awareness) in L2 development with a link to learning in the classroom setting. It approaches explicit L2 learning from five perspectives: theory, methodology, empirical work, model building, and pedagogy. It is theoretically based on mentalist or psycholinguistics SLA which posit that L2 development is more cognitive in nature. It also reviews studies which were motivated by cognitive accounts of SLA, more specifically studies on explicit L2 learning. It provides teachers with a model of L2 learning process in instructed SLA, and researchers with reviews on data elicitation procedures (online and offline) in SLA research. This book is written with novice teachers and researchers in mind, therefore it is both theoretical and practical in nature.